2008
DOI: 10.1002/ajmg.b.30668
|View full text |Cite
|
Sign up to set email alerts
|

Association of complement factor H Y402H gene polymorphism with Alzheimer's disease

Abstract: Alzheimer's disease (AD) and age-related macular degeneration (AMD) share several epidemiological and biochemical features. The present study aimed to assess the possible influence of the AMD-associated complement factor H (CFH) Y402H (1277T > C) polymorphism on the risk of AD. Caucasian subjects (n = 800) meeting the criteria for probable (n = 717) or definite (n = 83) AD and Caucasian non-demented controls (n = 1265) were included in this multi-center case-control study, in which genotype and allele frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 58 publications
3
51
1
1
Order By: Relevance
“…As a result, apoE2 is associated with type III hyperlipoproteinemia (33), and apoE4 is associated with, for example, Alzheimer disease (34). But apoE polymorphism is also associated with AMD, characterized by strong association with FH polymorphism Y402H within the domain 7, and these two polymorphisms could have an additive effect (35,36). It remains, however, to be studied whether the various apoE isoforms affect binding to FH.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, apoE2 is associated with type III hyperlipoproteinemia (33), and apoE4 is associated with, for example, Alzheimer disease (34). But apoE polymorphism is also associated with AMD, characterized by strong association with FH polymorphism Y402H within the domain 7, and these two polymorphisms could have an additive effect (35,36). It remains, however, to be studied whether the various apoE isoforms affect binding to FH.…”
Section: Discussionmentioning
confidence: 99%
“…Complement factor H regulates the formation of C3 and C5 convertase enzymes and the functional Tyr402His allele has been associated with Alzheimer's dementia in individuals carrying the APOE4 allele (Zetterberg et al, 2008). A case (PPMS n ¼ 53, RRMS n ¼ 212, SPMS n ¼ 85)-control (n ¼ 86) study of the Tyr402His allele of complement factor H found no difference in the allele frequency (Ingram et al, 2010).…”
Section: Complement Factor Hmentioning
confidence: 99%
“…The study material was in part the same as the one used in a number of previous publications (Zetterberg et al 2008;Landgren et al 2010;von Otter et al 2010avon Otter et al , 2010b and consisted of 713 AD cases and 841 individuals without dementia, all of Swedish nationality. Clinical diagnoses were set according to the National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association (NINCDS-ADRDA) criteria (McKhann et al 1984) after completion of a detailed clinical examination including medical history, physical, neurological and psychiatric examination, screening laboratory tests, ECG, EEG, chest X-ray and computed tomography of the brain.…”
Section: Methodsmentioning
confidence: 99%